Morphological Characteristics, Microscopical Characteristics, and Qualitative Phytochemical Screening of Murdannia nudiflora (L.) Brenan - Duc Loi, Vu; Hong Duong, Le; Thanh Huyen, Ngo; Thi Hien, Nguyen; Thi Hong Duong, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Murdannia nudiflora (L.) Brenan has been found in many provinces and cities, such as Lao Cai, Lang Son, Quang Ninh, Bac Giang, Phu Tho, Lam Dong, etc. This plant is known for its effects, such as anti-oxidation, protection of damaged liver cells, pain relief, anti-inflammation, and anti-cancer. In this study, we collected and determined the scientific name based on the analysis of morphological and microscopic characteristics of the Murdannia nudiflora collected in Phu Tho province. Then, we qualitatively screened some common groups of compounds in medicinal herbs. The study of botanical characteristics determined the scientific name of the plant as Murdannia nudiflora (family Commelinaceae). At the same time, a dataset of microscopic characteristics of stems and leaves of Murdannia nudiflora and their powder was built. In addition, qualitative results of the study showed that the species of Murdannia nudiflora contains groups of flavonoids, saponins, tannins, organic acids, alkaloids, coumarins, reducing sugars, sterols, and carotenes.